2004
DOI: 10.1007/s00204-004-0552-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of CYP1A1 in a Korean population

Abstract: Genetic polymorphisms in the coding exons of the CYP1A1 gene were analyzed in 100 Koreans. Three types of CYP1A1 polymorphisms, specifically G134A, G184C and A2455G, were identified with allelic frequencies of 18, 3, and 16%, respectively, and no linkage was observed among them. The novel G184C polymorphism identified in this study was associated with the mutation of an alanine residue at position 62 to proline. Other earlier-reported polymorphisms in the coding region of CYP1A1 were not detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In an earlier study, 13 nucleotide polymorphisms (at 12 positions: 3229, 3219, 134, 1636, 2414, 2453, 2455, 2461, 2500, 2546, 3205, and 3801) and one frameshift mutation due to a single-base insertion between 2346 and 2347 in CYP1A1 have been reported in the Korean population (Duk et al , 2004). Among these, nine polymorphisms were associated with amino acid substitutions (Spurr et al , 1987; Hayashi et al , 1991; Crofts et al ; 1993; Cascorbi et al , 1996; Smart and Daly, 2000; Chevalier et al , 2001; Saito et al , 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In an earlier study, 13 nucleotide polymorphisms (at 12 positions: 3229, 3219, 134, 1636, 2414, 2453, 2455, 2461, 2500, 2546, 3205, and 3801) and one frameshift mutation due to a single-base insertion between 2346 and 2347 in CYP1A1 have been reported in the Korean population (Duk et al , 2004). Among these, nine polymorphisms were associated with amino acid substitutions (Spurr et al , 1987; Hayashi et al , 1991; Crofts et al ; 1993; Cascorbi et al , 1996; Smart and Daly, 2000; Chevalier et al , 2001; Saito et al , 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Hence, the coordinated expression and regulation of phase I and II enzymes determine the outcome of carcinogen exposure. Sequence variations or polymorphisms in these genes can alter the expression, function and activity of these enzymes and, consequently, the cancer risks (Duk et al , 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The current case control study found novel substitution and frameshift mutations in pharyngeal and laryngeal cancer patients whereas no control had these mutations. Thirteen nucleotide polymorphisms in CYP1A1 gene have been reported by different researchers as cited in article by Park et al [13] th is a frame-shift mutation due to a single base insertion between 2346 and 2347. A study on Korean population of Asian origin found no already reported polymorphisms of CYP1A1 gene [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen nucleotide polymorphisms in CYP1A1 gene have been reported by different researchers as cited in article by Park et al [13] th is a frame-shift mutation due to a single base insertion between 2346 and 2347. A study on Korean population of Asian origin found no already reported polymorphisms of CYP1A1 gene [13]. Among these, nine polymorphisms were associated with amino acid substitutions [14].…”
Section: Discussionmentioning
confidence: 99%